Estudio para conocer el nivel de organización y su incidencia en las pequeñas y medianas empresas en la provincia de Cotopaxi. - Caisaguano Quishpe, Alex Marcelo (2020)
The present research project was made to Small and Medium Enterprises (PYMES) in the province of Cotopaxi, using research techniques and tools to collect data and information that will be analyzed and thus know the current situation, regarding the organizational level that the companies own, for this purpose it was necessary to resort to public institutions and thus obtain the total amount of the companies, partnerships and sole proprietorships that are in operation within the province, in addition it was necessary to use a descriptive research, for the elaboration and application of surveys using electronic means in the different PYMES, as well as the minimum legal requirements imposed by the authorities and governmental regulatory and control entities who guarantee that the products and services comply with the requirements in quality, safety, security and environmental care, for other side and without overlooking the possible effects and incidents that reduce the productive development of the different companies due to the different organizational gaps and the lack of the aforementioned obligations imposed by the authorities. Once the surveys were completed, they proceeded to their respective analysis and interpretation, and with this the level of organization that the companies have was established, in a qualitative way, using scales for the assignment of measurable values, and in this way to know the internal performance focusing on its organizational structure, processes, procedures, functions, permits, licenses, manuals, certifications, and in this way proposing adequate solutions to the exposed needs, which serve as support, to all companies, to reduce unnecessary costs, loss of times, and thus obtain better results in productivity, quality, safety, continuous improvement and environmental care.